A study on the stability and frying performance of used palm olein - effect of topping up / Nik Nurain Nik Hanafi - Nik Hanafi, Nik Nurain (2003)
This study investigated the stability, quality and frying performance of used palm olein and the effect of topping up during frying. The peroxide value (PV), free fatty acid (FFA), color, polar and polymer compounds of the used palm oleins were measured on the first, third and fifth days of frying to be correlated to the oxidative stability as determined by the Rancimat, overall oil quality and frying performance. Sensory evaluation of chicken nuggets and odor of oil were also conducted at the same time to determine consumer acceptability of both used palm oleins. The study indicated that the topped up used palm olein had higher oxidative stability and quality than the non-topped up used palm olein as shown by its lower PV, FFA, color, polar and polymer compounds and its higher induction period on the first, third and fifth days of frying. For the sensory evaluation of chicken nuggets fried in topped up and non-topped up used palm oleins, and the sensory evaluation of odor of oil, the results showed no significant differences (p>0.05) in terms of color, aroma, taste, texture, odor and overall acceptability on the first, third and fifth days of frying. Overall, the topped up used palm olein was better than the non-topped up used palm olein in terms of stability, quality and frying performance.